2012
DOI: 10.1016/j.ijgo.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Syncytiotrophoblast‐derived microparticle shedding in early‐onset and late‐onset severe pre‐eclampsia

Abstract: Shedding of STBMs into the maternal circulation occurs in greater amounts in early-onset pre-eclampsia than in late-onset pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 24 publications
4
63
0
2
Order By: Relevance
“…It is well documented that there is an increase in shedding of placental macrovesicles (SNAs) during preeclampsia (Attwood and Park 1961;Chua et al 1991;Buurma et al 2013). Similarly, the shedding of placental microvesicles into the maternal blood is also increased in women with early onset preeclampsia (Goswami et al 2006;Chen et al 2012b), with levels in the maternal blood correlating with systolic blood pressure (Lok et al 2008b). However, the level of circulating placental microvesicles does not seem to be altered in women with late onset preeclampsia or intrauterine growth restriction (Goswami et al 2006).…”
Section: The Production Of Placental Vesicles Is Increased In Preeclamentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that there is an increase in shedding of placental macrovesicles (SNAs) during preeclampsia (Attwood and Park 1961;Chua et al 1991;Buurma et al 2013). Similarly, the shedding of placental microvesicles into the maternal blood is also increased in women with early onset preeclampsia (Goswami et al 2006;Chen et al 2012b), with levels in the maternal blood correlating with systolic blood pressure (Lok et al 2008b). However, the level of circulating placental microvesicles does not seem to be altered in women with late onset preeclampsia or intrauterine growth restriction (Goswami et al 2006).…”
Section: The Production Of Placental Vesicles Is Increased In Preeclamentioning
confidence: 99%
“…von Dadelszen et al (1999) reported that the conditioned media derived from culturing endothelial cells with microvesicles from normal term placentae was proinflammatory and could activate resting monocytes, granulocytes, and lymphocytes (von Dadelszen et al 1999). It has also been shown that microvesicles derived from normal term placentae can inhibit proliferation and increase apoptosis of endothelial cells (Smarason et al 1993;Chen et al 2012b). Electron microscopic examination revealed extensive disruption of the usual honeycomb structure of the endothelium by placental microvesicles (Smarason et al 1993;Cockell et al 1997).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…6 The number of erythrocyte and endothelial MVs increases in severe PET, 7 and shedding of trophoblast MVs into maternal circulation is higher in early-onset than late-onset diseases. 8 It is of interest that MVs of women with PET were found to promote vascular wall inflammation. 9 Our previous study, characterizing MVs of normal healthy pregnant (NHP) women and women with gestational vascular complications (GVCs), including HT and PET, 10 showed that trophoblast MV levels were similar in these groups.…”
Section: Hypertensionmentioning
confidence: 99%
“…MV concentrations were measured using 7.5 µm count beads (Flow Cytometer Absolute Count Standard, Bangs Laboratories Inc., Indiana), as described previously. 8 . MVs were labeled with antibodies for 30 minutes, suspended in PBS containing 0.02% formaldehyde, and scanned by the CyAn ADP analyzer.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Syncytiotrophoblast extracellular vesicles (STBM) are continuously shed and secreted from the placental syncytium into the maternal circulation in normal pregnancy. Significantly increased amounts of STBM have been discovered in PE [6], especially in early-onset PE [7,8]. STBM mainly comprise microparticles and exosomes, which vary in size, morphology and function.…”
Section: Introductionmentioning
confidence: 99%